Involuntary Associations Postcolonial Studies and World Englishes - Huddart, David (Postcolonialism Across the Disciplines, 2014)
The consequences of Englishes spread have become increasingly clear to its diverse speakers. Sometimes associated with a standardization leading to homogenization, often also with imperialism, English is increasingly understood to have no necessary connection with any country or group of countries. The willingness to accept that English has become Englishes might be less evident among so-called native speakers, but their authority is weaker than it seemed. This book puts examples from World Englishes into dialogue with postcolonial studies. The dialogue will correct misconceptions and misapprehensions in postcolonial studies, with World Englishes offering renewal for postcolonial studies. At the same time, the dialogue will also apply postcolonial studies' political and philosophical ideas to World Englishes, resulting in a postcolonial perspective on English today.